Nutrient sources and loads in the River Derwent catchment, Tasmania. Issue 2 (3rd April 2022) - Proemse, Bernadette C.; Koolhof, Iain; White, Richard; Barmuta, Leon A.; Coughanowr, Christine
ABSTRACT: The greater River Derwent catchment is one of the largest river basins in Tasmania, Australia, and is the main supply of drinking water to the state's capital, Hobart. Recently, summer-time occurrence of blue-green and filamentous algal blooms, combined with taste and odour problems at the drinking water intake, have raised concerns regarding the river's water quality. In order to develop nutrient management strategies, it is crucial to understand nutrient sources and loads. This article therefore determines nutrient production loads using point source effluent data combined with estimates for diffuse sources using land-use data. Overall, we found that aquaculture is the main point source of total nitrogen (TN) and total phosphorus (TP) compared to sewage treatment plants, while agriculture is the main diffuse source of TP and forestry the main diffuse source of TN in the catchment overall. These estimates are compared to river mass loads derived from a two-year monitoring program, revealing some discrepancies between estimated and measured loads for some of the sub-catchments. Our findings identify priority areas for improved nutrient management and highlight the need for more frequent and continuous water quality monitoring to help reduce uncertainties for estimating nutrient loads in the River Derwent catchment.